2012
DOI: 10.1016/j.bmc.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of potent and selective human V1a receptor antagonists as potential ligands for PET or SPECT imaging

Abstract: SRX246 is a potent, highly selective human vasopressin V1a antagonist that crosses the blood–brain barrier in rats. CNS penetration makes SRX246 an ideal candidate for potential radiolabeling and use in visualization and characterization of the role of the V1a receptor in multiple stress-related disorders. Before radiolabeling studies, cold reference analogs of SRX246 were prepared. This study describes the synthesis and in vitro screening for human V1a receptor binding and permeability of fluoro, iodo, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The lack of comparative studies in non-human and human primates with specific ligands and proper number of subjects highlights the need for further investigation into potential sex differences in brain V1aR expression in these species. Recently, a radiolabeled human V1aR antagonist has been developed for the use in PET and SPECT imaging, which may lead to a further understanding of sex differences in the brain V1aR system in humans, including the potential relation of V1aR binding with brain function and vasopressin-related disorders (Fabio et al, 2012). …”
Section: Sex Differences In Vasopressin and Oxytocin Receptors In mentioning
confidence: 99%
“…The lack of comparative studies in non-human and human primates with specific ligands and proper number of subjects highlights the need for further investigation into potential sex differences in brain V1aR expression in these species. Recently, a radiolabeled human V1aR antagonist has been developed for the use in PET and SPECT imaging, which may lead to a further understanding of sex differences in the brain V1aR system in humans, including the potential relation of V1aR binding with brain function and vasopressin-related disorders (Fabio et al, 2012). …”
Section: Sex Differences In Vasopressin and Oxytocin Receptors In mentioning
confidence: 99%
“…Synthesis of compounds 8a-l was achieved by the Suzuki reaction of the iodo-intermediates 3a, 3c-d with commercially available boronic acids or in-house prepared boronic esters 7 ( Schem e 3) [21].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study [21] described the first V 1a PET radiotracers, but imaging studies in animals with these radiotracers have not been reported, possibly because of the suboptimal molecular weights (700–800 Dalton) of the radiotracers for sufficient blood-brain barrier permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Fabio et al 34 have developed a reliable method to prepare a versatile precursor that should allow access to both PET (18F, 11C) and SPECT (123I) derivatives of SRX246 {(R)-4-([1,4-Bipiperidin]-10-yl)-2-((2R,3S)-2-((E)-3-substitutedstyryl) -4 -oxo-3-((S)-2-oxo-4-phenyloxazoli din -3 -yl) azetidin-1-yl) -4 -oxo -N -((R) -1 -phenylethyl) Butanamides}29, a highly selective and potent hV1a antagonist.…”
Section: Vasopressin Via Antagonistmentioning
confidence: 99%